2010
DOI: 10.1016/j.devcel.2010.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of a Plant Stem Cell Niche

Abstract: Despite the independent evolution of multicellularity in plants and animals, the basic organization of their stem cell niches is remarkably similar. Here, we report the genome-wide regulatory potential of WUSCHEL, the key transcription factor for stem cell maintenance in the shoot apical meristem of the reference plant Arabidopsis thaliana. WUSCHEL acts by directly binding to at least two distinct DNA motifs in more than 100 target promoters and preferentially affects the expression of genes with roles in horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
216
3
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(234 citation statements)
references
References 76 publications
12
216
3
3
Order By: Relevance
“…Nonetheless, it is interesting to note that the transcriptional repression functions of both STF and WUS are required to activate cell proliferation. In the Arabidopsis shoot apical meristem, WUS has several direct targets (23), including the well-studied CLAVATA regulatory feedback loop (7), in which WUS directly represses CLV1 (23), and cytokinin signaling, in which WUS directly represses A-type two-component response regulators (24). Whether STF shares any of these regulatory modules to promote cell proliferation in leaf primordia is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is interesting to note that the transcriptional repression functions of both STF and WUS are required to activate cell proliferation. In the Arabidopsis shoot apical meristem, WUS has several direct targets (23), including the well-studied CLAVATA regulatory feedback loop (7), in which WUS directly represses CLV1 (23), and cytokinin signaling, in which WUS directly represses A-type two-component response regulators (24). Whether STF shares any of these regulatory modules to promote cell proliferation in leaf primordia is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, WUS has been shown to bind cis elements containing TAAT core sequences in the regulatory regions of activated target genes CLV3 (6) and AGAMOUS (24) as well as in the regulatory regions of repressed target genes (14,18,19). However, the mechanisms through which WUS can discriminate between transcriptional activation and repression by using similar cis elements are not understood.…”
Section: Significancementioning
confidence: 99%
“…Several studies have shown that WUS also represses the transcription of many genes (14,18,19), including several differentiationpromoting transcription factors, thus preventing premature differentiation of stem cell descendants (19). The transient transcriptional assays in Arabidopsis leaf protoplasts have shown that WUS can function as both an activator and a repressor (20).…”
mentioning
confidence: 99%
“…In Arabidopsis, ChIP-chip/Seq has been applied to a range of TFs, primarily those active in flowering and development. Because of the static nature of a ChIP experiment (it is a snapshot of the biological state), the genome-wide profiling of TF-binding sites is often combined with differential expression analysis in a knockout Morohashi and Grotewold, 2009;Busch et al, 2010;Yant et al, 2010) or an inducible overexpression line (Thibaud-Nissen et al, 2006;Kaufmann et al, 2009Kaufmann et al, , 2010Mathieu et al, 2009). By combining these two data types, TF target interactions can be viewed with respect to the expression of both the TF and the target, thus transforming the static ChIP image to a set of dynamic transcriptional modules.…”
mentioning
confidence: 99%